Bathe the Cat - McGinty, Alice B., 1963-; Roberts, David, 1970- (San Francisco : Chronicle Books, 2021)
Dad has posted a list of chores for the family to do before grandma comes, including bathing the cat; but the cat does not want a bath, so she mixes up the instructions, and soon the family is mowing the floor, vacuuming the lawn, mopping the baby--and the house is in chaos.
Ages 3-5.
Grades K-1.
Keywords: Cats -- Juvenile fiction; Chores -- Juvenile fiction; Families -- Juvenile fiction; Stories in rhyme; Stories in rhyme; Chores -- Fiction; Family life -- Fiction; Gay fathers -- Fiction; Cats -- Fiction; Stories in rhyme; Humorous fiction